Psychoanalysis and theology: Two dialectics - Hackett, Charles D. (Journal of religion and health, 1986)
In the vocabulary of psychoanalysis, "health" means something roughly correlative to "salvation" in the vocabulary of theology. Both health and salvation assume some manner of change from a previous pathological or doomed state. Against this background this paper seeks to delineate two different possible models of change: One in which realityper se is changed as opposed to one in which theperception of reality is changed. In theology, the former can be represented by Paul and the latter by John. In psychoanalysis, Freud represented each point of view in his structural and topographical paradigms respectively. In contemporary psychoanalytical therapy, Otto Kernberg represents the former and Jacques Lacan the latter.